Determinants of Farmers' Land Use Decision-Making: Comparative Evidence From Thailand and Vietnam. (January 2017) - Nguyen, Trung Thanh; Nguyen, Loc Duc; Lippe, Rattiya Suddeephong; Grote, Ulrike
Highlights: Factors affecting farmers' land use decision-making are examined. Econometric models are applied to panel data collected in 2007 and 2013. Crop diversification is a weather shock-coping strategy of households. Land reconsolidation and privatization reduce farmers' vulnerability. Summary: Understanding farmers' land use decision-making is of interest to policy makers and scientific communities. Furthermore, comparing farmers' land use decision-making between countries offers a functioning instrument to enhance this understanding, since one country can benefit from the experiences of another. This study extends the sustainable livelihoods framework to examine and compare the factors affecting farmers' land use decision-making regarding land use choices and crop diversification. A panel dataset of 514 farm households in Ha Tinh (Vietnam) and 422 farm households in Ubon Ratchathani (Thailand) collected in 2007 and 2013 is used for the analyses. The results reveal that (i) farmers' land use decision-making is determined by various factors representing the livelihood platforms, weather shock experience and expectation, and physical-economic conditions of the living localities, and (ii) crop diversification is a weather shock-coping strategy of rural households. We suggest that (i) promoting farm land reconsolidation and privatization, (ii) enhancing access to credit sources and national electricity networks, and (iii) improving rural road conditions and attracting investments in rural non-agricultural sectors contribute to reducing farmers' vulnerability to climate variability.